The September 2002 Antarctic vortex major warming as observed by visible spectroscopy and ozone soundings - Yela, M.; Parrondo, C.; Gil, M.; Rodríguez, S.; Araujo, J.; Ochoa, H.; Deferrari, Guillermo Alejandro; Diaz, Susana Beatriz (International Journal of Remote Sensing)
The record of O3 total column and NO2 obtained by visible spectroscopy at Ushuaia (55° S), Marambio (64° S) and Belgrano (78° S) and vertical ozone profiles from the latter station provide insight into the unprecedented major warming observed above Antarctica in the last week of September 2002. From 18 September to 25 September the temperature increased 54°C at the isentropic level of 700 K. The temperature anomaly was observed down to the level of 300 K in which a well-defined tropopause was established. From comparison of the ozone profiles before and during the event, it can be seen that a fast increase in O3 took place basically above 500 K, but the layer where the ozone hole occurs was barely affected. Low potential vorticity values above Belgrano occurred only at levels above 500 K, confirming that the vortex split was confined to heights above the layer of the Antarctic spring depletion. The signature of poleward-transported air is clearly visible from the NO2 column departure from the envelope of the previous years in all three stations. NO2 columns larger than typical for ozone hole conditions by 400% were observed at Belgrano. Diurnal variations provide evidence of non-denitrified extra-vortex air. Fil: Yela, M. Instituto Nacional de Técnica Aeroespacial; España Fil: Parrondo, C. Instituto Nacional de Técnica Aeroespacial; España Fil: Gil, M. Instituto Nacional de Técnica Aeroespacial; España Fil: Rodríguez, S. Instituto Nacional de Técnica Aeroespacial; España Fil: Araujo, J. Dirección Nacional del Antártico; Argentina Fil: Ochoa, H. Dirección Nacional del Antártico; Argentina Fil: Deferrari, Guillermo Alejandro. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina Fil: Diaz, Susana Beatriz. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Austral de Investigaciones Científicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Investigaciones en Ingeniería Genética y ...